Exploring discovery : the front door to your library's licensed and digitized content - Varnum, Kenneth J., 1967- (Chicago : ALA Editions, an imprint of the American Library Association, 2016)
The pace of change in recent decades has been dizzying. An index of books was a static item; discovery might require searching several places to find both the index and the item. Now the variety of materials managed and collected by individual librarys is expansive, and the concept of'discovery' can cover hundreds, thousands or even billions of items. Where is'discovery' going... and how will it change your life?
Collaborative growth toward discovery : becoming stronger through change / Margaret Heller and Hong Ma -- Approaching discovery as part of a library service platform : lessons learned / Nathan Hosburgh -- When you rent your front door : a mid-size library's experiences relying on discovery vendors / Stephen Bollinger and Kate Silton -- Exploring discovery at Rosenberg Library : what happens when a library, a museum, and an archive get together to share a single discovery tool? / T. Louise M. Kidder -- Geospatial resource discovery / Darren Hardy, Jack Reed, and Bess Sadler -- Discovery on a shoestring : implementing a full-functioned discovery tool with free software and no-extra-charge metadata sources / Julia Bauder -- Agile open-source discovery : Blacklight with EBSCO Discovery Service / Sam Popowich -- Using Blacklight for archival discovery / Adam Wead and Jennie Thomas -- Creating a'magical' request and delivery experience for patrons using a Blacklight-based catalog / Matthew Connolly, Jennifer Colt, Joanne Leary, and Melissa Wallace -- The bento box design pattern / Jason Thomale, William Hicks, and Mark Phillips -- One-to-many : building a single-search interface for disparate resources / Cole Hudson and Graham Hukill -- Integrating discovery to improve the user experience / Sonya Betz and Ian Roberton -- Fixing facets / Sean Hannan, Steven Heslip, and Kristen Johannes -- One size doesn't fit all : tailoring discovery through user testing / Joseph Deodata, Khalilah Gambrell, and Eric Frierson -- From user stories to working code : a case study from NYU's digital collections discovery initiative / Daniel Lovins -- Regional aggregation and discovery of digital collections : the Mountain West Digital Library / Anna Neatrour, Rebekah Cummings, and Sandra McIntyre -- Open Access and discovery tools : how do Primo libraries manage green open access collections? / Fran's Renaville -- Discovery platforms and the database of record / Alan Manifold -- Know thy metadata : metadata challenges in discovery services / Myung-Ja K. Han and William Fletcher Weathers.
Includes bibliographical references and index.
Keywords: Electronic information resource searching; Federated searching; Information retrieval -- Computer programs; User interfaces (Computer systems); Libraries -- Special collections -- Electronic information resources; Electronic information resources -- Management